LIMITED ATONEMENT DAN PENGINJILAN: Suatu Tinjaun Historis - Timotius Timotius; Oey Natanael Winanto (Didache: Jurnal Teologi dan Pendidikan Kristen, 2021)
Evangelism is the great mandate of the Lord Jesus before going up to heaven. However, several problems arose related to the concept of evangelism. This happens when the concept of evangelism is associated with a limited redemption doctrine in Reformed theology. The question is whether limited redemption doctrine has prevented evangelism? Harold Dekker said that, limited redemption doctrine had hindered the activity of evangelism in the Reformed Church. According to Dekker, this is because the limited redemption doctrine has made Reformed people no longer say that Jesus died for you to people who do not believe. This paper will explore the history of evangelism carried out by the Reformed Church to prove that limited redemption doctrines do not hinder the activity of reformed church evangelism.   Penginjilan merupakan Amanat Agung Tuhan Yesus sebelum naik ke surga. Namun, muncul beberapa masalah berkaitan dengan konsep penginjilan. Hal itu terjadi ketika konsep penginjilan dikaitkan dengan doktrin penebusan terbatas dalam teologi Reformed. Pertanyaannya adalah apakah doktrin penebusan terbatas telah menghalangi penginjilan? Harold Dekker mengatakan bahwa, doktrin penebusan terbatas telah menghalangi aktifitas penginjilan dalam gereja Reformed. Menurut Dekker, hal itu dikarenakan doktrin penebusan terbatas telah membuat orang-orang Reformed tidak bisa lagi mengatakan bahwa Yesus mati bagimu kepada orang yang belum percaya. Karya tulis ini akan menelusuri sejarah penginjilan yang dilakukan oleh gereja Reformed untuk membuktikan bahwa doktrin penebusan terbatas tidak menghalangi aktifitas penginjilan gereja Reformed.